Tathwīr al-Mādatu an-Nahwiyah bi al-Madkhal Tafā ‘ulī li Tarqiati Fahmi Jumalu al-Lughoh al-‘Arobiyyah / The Developing of Nahwu in The Interactive Approach to Improve The Understanding of The Structure of The Arabic Language - Lailatul Zuhriyah; Arwan Rifa’i (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2021)
Nahwu learning model in many educational institutions, including at islamic schools level, is still traditional based on theory of behaviorism in which students are passive in the learning process so that it affects students' low motivation and ability to apply the Nahwu theory learned to Arabic language skills. Therefore, Nahwu learning should be designed based on the interactive methode to make students more active in the learning process so that their learning motivation and outcomse can increase, especially to improve learning in science and social studies majors in reading text Arabics discourse by nahwu at Madrasah Ibtidaiyah 3 Kandangan Kediri. The research and development methode used the Borg and Gall development model. Produce the design of learning nahwu on high order the understanding text skills with concept maps, songs, and sentence of arabic games. And the results of the research: based on the evaluation of experts, the teacher and the students that the validity of the model is “very good” (94.03% and 91.47%) for the design expert, the book and the compiler of the result is the grammar expert “good” (82.85% and 80.71), 83 , 03% of the students, then the t-statistic result = 4,021 and the result from the t-cound found that the result = 1,998 at the 5% moral level, and 2,655 at the 1% level. And because the statistic result of 4,021 is greater than the result at the moral level 5%. Keywords: Development, Nahwu, Interactive Approach, The Sentence’s Of Arabic Language. ملخص نموذج تدريس النحو في كثير من التربوية بما في ذلك المستوى المدارسي الإسلامي لا يزال تقليديا القائم على النظرية السلوكية حيث أن موقف الطلبة غير متفاعلين في عملية التعليم والتعلم، حتى يؤثر إلى انخافض دافعية الطلبة وقدراتهم في تطبيق علوم النحو التي تمت دراستها لمهارتهم العربية. ثم لابد من أن يصمم تدريس النحو القائم على المدخل التفاعلي ي يكون الدارس أكثر تفاعلا في علمية التعليم والتعلم حتى ترفع دافعية الطلبة وتحصيلهم الدراسي، الأفضال ترقية فهم النص العربي للطلبة الأولى بقسم العلوم الطبعية والعلوم الإجتماعية بألة علم النحو في المدرسة الإسلامية الحكومية 3 كاندانجان كديري. يسخدم هذا البحث والتطوير نموذج تطوير Borg & Gall. وإنتاج تصميم تعليم النحو العربي بناء على مهارات فهم النصوص العربية بإستخدام جدوال النحو والغناء ولعبة النحو أولا. وأما نتائج البحث: بناء على تقييم الخبراء والمدرس ولطلبة أن صدق النموذج